2005
DOI: 10.1021/ie0507427
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adsorption in the Permeation of CH4 and CO2 through a Silicalite-1 Membrane

Abstract: The role of adsorption in the single and binary permeation of CH4 and CO2 through a silicalite-1 membrane has been investigated. Adsorption on the zeolite is favorable for CO2, resulting in selectivity for CO2 in the permeation. The generalized Maxwell−Stefan (GMS) equations, in combination with the ideal adsorbed solution theory (IAST), were used to model their binary permeation. It is found that the use of accurate adsorption data is of utmost importance for extracting transport properties from the single-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
115
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 46 publications
7
115
0
Order By: Relevance
“…Figure 2 shows good agreement between our computed isotherm for N 2 at 308 K and the one of Goj et al (2002). Similar good agreement is observed between the data obtained in this work for CO 2 and the experimental measurements of Zhu et al (2006), Hirotani et al (1997), Sun et al (1998), andChoudhary et al (1996). Adsorption isotherms of CO 2 , CH 4, and N 2 in MOR were computed at 300 K and 210 K and compared with the isotherms of Delgado et al (2006) and Webster et al (1999) as shown in Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Figure 2 shows good agreement between our computed isotherm for N 2 at 308 K and the one of Goj et al (2002). Similar good agreement is observed between the data obtained in this work for CO 2 and the experimental measurements of Zhu et al (2006), Hirotani et al (1997), Sun et al (1998), andChoudhary et al (1996). Adsorption isotherms of CO 2 , CH 4, and N 2 in MOR were computed at 300 K and 210 K and compared with the isotherms of Delgado et al (2006) and Webster et al (1999) as shown in Fig.…”
Section: Resultssupporting
confidence: 85%
“…2 Computed (Sim) and measured (Exp) adsorption isotherms of CO 2 and N 2 in MFI-type zeolite. Previous experimental (Choudhary and Mayadevi 1996;Hirotani et al 1997;Sun et al 1998;Zhu et al 2006) and simulation (Goj et al 2002) data are included for comparison with experiments in all range of pressures. The small discrepancies between our results and the experimental values are attributed to the Si/Al ratio of the MOR structures used in the experimental measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the adsorption parameters of CO 2 determined by the LCM-based adsorption measurement device in this work compare well to values reported in literature [9][10][11][12] , i.e., the adsorption capacity, adsorption enthalpy and adsorption entropy reported for CO 2 in MFI-type zeolites vary in the range of 2.1-3.8 mmol g …”
Section: Adsorption Measurements Notesupporting
confidence: 89%
“…Furthermore, the stainless-steel-net has open voids and the first layer of the membrane is almost b-oriented which facilitates easy access to the straight-channels of zeolite silicalite-1, as a result the CO 2 permeation factors are much higher than those reported to date. [29][30][31] In the Supporting Information, it is also noted that the separation factors of mixture gas are much higher than the ideal separation factors. It can be deduced that the preferred adsorption of CO 2 blocks the flow of N 2 , H 2 , CH 4 molecules through the zeolite silicalite-1 channels of the membrane.…”
mentioning
confidence: 99%